Transcription factors Foxo3a and Foxo1 couple the E3 ligase Cbl-b to the induction of Foxp3 expression in induced regulatory T cells - Harada, Yohsuke (The Rockefeller University Press, 2010)
The transcription factor Foxp3 is essential for optimal regulatory T (T reg) cell development and function. Here, we show that CD4(+) T cells from Cbl-b RING finger mutant knockin or Cbl-b–deficient mice show impaired TGF-β–induced Foxp3 expression. These T cells display augmented Foxo3a phosphorylation, but normal TGF-β signaling. Expression of Foxo3a rescues Foxp3 expression in Cbl-b–deficient T cells, and Foxo3a deficiency results in defective TGF-β–driven Foxp3 induction. A Foxo3a-binding motif is present in a proximal region of the Foxp3 promoter, and is required for Foxo3a association. Foxo1 exerts similar effects as Foxo3a on Foxp3 expression. This study reveals that Foxo factors promote transcription of the Foxp3 gene in induced T reg cells, and thus provides new mechanistic insight into Foxo-mediated T cell regulation.